Xamarin Mobile Application Development for Android - Reynolds, Mark (Packt Publishing, 2014)
A step-by-step tutorial that follows the development of a simple Android app from end to end, through troubleshooting, and then distribution. The language used assumes a knowledge of basic C#.If you are a C# developer with a desire to develop Android apps and want to enhance your existing skill set, then this book is for you. It is assumed that you have a good working knowledge of C#, .NET, and object-oriented software development. Familiarity with rich client technologies such as WPF or Silverlight is also helpful, but not required
Description based on publisher supplied metadata and other sources
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Open source software